Transgression and Taboo: The Field of Fan Fiction - Kirk, Jens (Academic Quarter | Akademisk kvarter, 2011)
Other transgressions on the Internet are discussed by Jens Kirkin his article Transgression and Taboo, where he argues that fan fiction is a genre which transgresses readers’ favourite source texts in order to produce their own fiction, thereby changing readers from consumers to producers. At the same time, certain boundaries of the source texts must also be upheld, so that a fundamental distinction between fan and author may be maintained.